Product inovation, interactive learning and economic performance - Christensen, Jesper Lindgaard; Lundvall, Bengt-ôke, 1941- (Emerald, 2004)
The aim of this book is to contribute to the understanding of product innovation - how it takes place and how it affects firms and the economy. It links product innovation to interactive learning and to the performance of firms. It studies the interconnections between these three elements on the basis of unique data sets and detailed case studies. The book will prove helpful for managers, employees and policy makers as well as for scholars and students who want to understand the role of product innovation in the economy.In the book it is shown that product innovation is of major importance. For the economy as a whole, the introduction of new products is fundamental for economic growth. Process innovation without product innovation would sooner or later result in economic stagnation and in what has been called technological unemployment. In turbulent sectors product innovation is necessary for firms to survive and grow. The book also shows that product innovation is a complex and multi-dimensional phenomenon. In order to capture this complexity authors combine different theoretical perspectives, different levels of aggregation, and different methodological approaches.
Keywords: Technological innovations -- Management.; Technology -- Management.; elektronické knihy; electronic books